Kinetics of Polychlorinated Biphenyl Biodegradation Using Biofilm Grown on Biphenyl - Josephine Borja; Joseph Auresenia; Susan M. Gallardo (Department of Chemical Engineering, Universitas Gadjah Mada, 2006)
The kinetics of polychlorinated biphenyl (PCB) degradation in a completely mixed three-phase fluidized-bed biofilm reactor was studied using an initial PCB concentration of 40 ppm. The mixed-culture biofilm grown on cement balls was gradually acclimatized to PCBs prior to the experimental runs. The time course of PCB concentration was monitored and the data obtained were fitted to first, second, and third order rate equations. Analysis of data was based on the assumptions that the PCB concentration was rate limiting and the mixed liquor volatile solids (MLVS) represents the active biomass. Linear regression analysis conducted for the 11 experimental runs show that PCB degradation does not follow first order kinetics. The best fit was obtained for second order in the first six runs when the overall PCB degradation was 80-85% (8-6 ppm final concentration). When the overall degradation increased to 89-92% (4-3 ppm final concentration) from run 7 onwards, the third order gave the best fit. The improved performance of the biofilm to degrade PCBs resulted in a kinetic rate pattern, which shifted from second to third order as the concentration of the PCBs dropped. The rate of PCB degradation was influenced by the presence of mixed culture whose combined attack on and long contact with PCBs resulted in PCB degradation that progressed from one batch to the next.